Experimental Study on Gangue Backfilling Materials Improved by Soda Residue and Field Measurement of Surface Subsidence - Yin, Wei; Zhang, Kun; Ouyang, Shenyang; Bai, Xiaomin; Sun, Wenjie; Zhao, Jingru (Frontiers in Earth Science, 2021)
In coal mining, the problems of massive discharge of solid waste, environmental pollution, and surface subsidence disaster are urgent to be solved. Based on this engineering background, the feasibility of using solid waste soda residue to improve gangue cemented backfilling material was discussed, and the surface subsidence of the test working face was measured in this study. Besides, the influence of soda residue on the performance of gangue cemented backfilling materials was analyzed through laboratory tests. The experimental results show that 1) as the content of soda residue increases within the range of 0–12%, the slump of the soda residue gangue backfilling material (SRGBM) slurry gradually increases, and the bleeding rate increases. The early strength and later strength of SRGBM increase first and then decrease with the increase in soda residue content. 2) The optimal ratio of the soda residue cemented backfilling material is soda residue: fly ash: lime: cement: gangue = 6%: 34%: 10%: 2.5%: 47.5%. Compared with the reference group, the slump of the material is increased by 12.7%, the bleeding rate is only 3.8%, and the early strength and later strength are increased by 449 and 187%, respectively. 3) The addition of soda residue promotes the hydration reaction of the slurry system of soda residue cemented materials. The coexistence of C-S-H gel and N-A-S-H gel reduces the connectivity of pores and improves the strength of the material. 4) The maximum surface subsidence of the test working face is only 245 mm, and the surface subsidence control effect is good. Therefore, the preparation of SRGBM with soda residue can achieve energy saving and emission reduction, with significant technical, economic, and social benefits, and has good promotion and application value.